Impact of Informal Electronic Waste Recycling and Dumping Activities on Soil Ecosystems: A review from 2000 to 2024 - N. H. T. Ly; T. T. K. Hong; N. T. Giao (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to examine the impact of informal electronic waste recycling and dumping activities on soil ecosystems: a review from 2000 to 2024 using domestic and foreign studies related to electronic waste issues on soil ecosystems from various scientific databases. The results showed that toxic metals and other pollutants in e-waste are released into the environment from improper disposal and informal e-waste recycling and treatment. These toxic substances eventually penetrate into soil, water, air and sediments leading to adverse effects on organisms in soil and water, causing toxicity to plants, and accumulating in the tissues of organisms and gradually amplifying along the food chain. It also seriously affects human health through exposure routes such as eating, breathing and absorbing through the skin. The findings of this review provided an overview of the toxic substances in e-waste affecting different components in the soil, water and air environment.